Islamic Counselling in the Generation Z Era: Strategies for Strengthening Work Ethic and Youth Resilience amid Social and Digital Disruption - Zulamri Zulamri; Rosmita Rosmita; Miftahuddin Miftahuddin; Kodarni Kodarni (Program Studi Bimbingan dan Konseling Islam, 2026)
The rapid advancement of digital technology and social transformation has significantly shaped the mindset, work patterns, and psychological resilience of Generation Z. While the digital era provides broad opportunities for creativity and access to information, it also brings challenges such as value disruption, instant culture, intense competition, and psychosocial vulnerability. This article analyzes the role of Islamic counselling in strengthening the work ethic and resilience of Generation Z amid digital disruption. This study employs a qualitative descriptive research design based on a literature review, drawing upon classical and contemporary sources on Islamic counselling, developmental psychology, and the characteristics of Generation Z. The findings reveal that Islamic counselling contributes to developing a value-oriented work ethic grounded in spiritual principles such as intention (niyyah), trustworthiness (amanah), excellence (ihsan), and responsibility. It also promotes resilience through cultivating meaning in life, patience (ṣabr), reliance on God (tawakkul), and awareness of higher purpose. Effective counselling strategies include contextual engagement with digital realities, adaptive media utilization, integration of Qur’anic and Prophetic values in communicative language, and empathetic guidance. Islamic counselling thus serves not only as psychological support but also as a framework for character formation, enabling Generation Z to adapt productively and ethically in a rapidly changing digital society.